Urinary tract infection pathogens diagnosed in Basra city hospitals - Suaad A. LAFTA; Alaa H. ABED; Maysoon K. IBRAHIM (Romanian Journal of Medical Practice)
Background. Urinary tract infection (UTI) is the growth of pathological bacteria within the urinary tract, and is one of the most common types of bacterial infections worldwide. Bacterial resistance to antibiotics is a major public health concern. Antibiotic-resistant bacterial infections exacerbate the situation in developed, developing and underdeveloped countries. Objective. The aim of this research is to identify the frequency of different bacterial pathogens and their sensitivity to different types of antibiotics in patients suffering from UTI in Basra city hospitals. Method. This cross-sectional study included 505 samples positive for bacterial growth. It was conducted by data extraction from hospital laboratory records, where information was obtained about bacterial examination of urine samples taken from patients with urinary tract infection. The samples were cultured and antibiotic sensitivity was tested by laboratory workers, in order to determine the appropriate treatment for patients. Results and conclusions. The average age of patients was 43.5 years, of whom (60.4%) were females. The most common bacteria was Escherichia coli (40.6%). In antibiotic susceptibility testing process, gentamicin (5.7%), ciprofloxacin (4.7%), trimethoprim (4.7%), trimethoprim/sulfamethoxazole (4.1%), and cefepime (3.9%) were the most frequently used antibiotics, while cefotetan (0.06%), ampicillin-sulbactam (0.09%), mupirocin (0.2%), cefazolin (0.2%), fosfomycin and amoxicillin (0.2%) were the least used. The highest sensitivity shown by cultured bacteria was to linezolid (95.5%), ertapenem (91.7%), teicoplanin (79.4%), nitrofurantoin (75.2%) and amikacin (72.4%). The highest resistance shown by cultured bacteria was to cefazolin (100%), oxacillin (94.6%), fusidic acid (91.2%), ampicillin (90.4%), and amoxicillin (88.2%).